2018
DOI: 10.3389/fmicb.2018.01756
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Extended-Spectrum β-Lactamase-Producing Multidrug Resistant Escherichia coli From Swine in Northwest China

Abstract: Objectives: The aim of the present study was to explore the prevalence and molecular characterization of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli collected from pig farms in Northwest China.Methods: Between May 2015 and June 2017, a total of 456 E. coli isolates were collected from fecal samples of healthy and diarrheal pigs in Northwest China to screen the ESBL producers. The β-lactamases, plasmid-mediated quinolone resistance (PMQR) genes and virulence genes among ESBL producers were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 45 publications
10
40
3
Order By: Relevance
“…All ESBL producers demonstrated multidrug resistance profiles. It is higher than that found in previous similar studies in pigs (9.6%) and surface waters (2.8%) in Shaanxi Province ( Liu, et al., 2018 ), whereas remarkably lower than that in dogs (24.2%) and retail foods (22.3%) in Shaanxi Province ( Xi et al., 2015 , Liu et al., 2016 ). In addition, among the E. coli analyzed in this study, the prevalence of ESBL producers (13.2%) is considerably lower than that previously found in chickens in Henan Province (60.8%) during 2007 to 2008 ( Yuan, et al., 2009 ) and Northeast China (Heilongjiang, Jilin and Liaoning Province, 100%) during 2011 to 2013 ( Tong, et al., 2015 ).…”
Section: Discussioncontrasting
confidence: 69%
“…All ESBL producers demonstrated multidrug resistance profiles. It is higher than that found in previous similar studies in pigs (9.6%) and surface waters (2.8%) in Shaanxi Province ( Liu, et al., 2018 ), whereas remarkably lower than that in dogs (24.2%) and retail foods (22.3%) in Shaanxi Province ( Xi et al., 2015 , Liu et al., 2016 ). In addition, among the E. coli analyzed in this study, the prevalence of ESBL producers (13.2%) is considerably lower than that previously found in chickens in Henan Province (60.8%) during 2007 to 2008 ( Yuan, et al., 2009 ) and Northeast China (Heilongjiang, Jilin and Liaoning Province, 100%) during 2011 to 2013 ( Tong, et al., 2015 ).…”
Section: Discussioncontrasting
confidence: 69%
“…E. coli strains of the ST10 have been frequently associated with UTI in several countries, including Brazil (Gonçalves et al, 2016 ; Hertz et al, 2016 ; Campos et al, 2018 ). Other studies have also reported the isolation of E. coli strains of the ST10 from the environment and food, as well as from bloodstream infections and diarrhea, evidencing the versatility of colonization of this ST (Arais et al, 2018 ; Liu et al, 2018 ; Mohsin et al, 2018 ; Yamaji et al, 2018 ).…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, plasmid-mediated quinolone resistance (PMQR) genes are associated with ESBL production, and the spread of co-expressing PMQRs and ESBL isolates contributes to the growing concerns regarding MDR isolates. 21 Also, hvKp strains are of major importance as they are hypervirulent and highly transmissible. 18 …”
Section: Introductionmentioning
confidence: 99%